Some Aspects of Reproductive Biology of the Mudskipper Apocryptes Bato From the Coast of Chitagong - Rahman, Mohammed Sadequer; Parvez, Md Sohel; Rahman, Mohammad Mizanur; Nabi, Md Rashed un; Alam, Md Wahidul (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Some aspects of reproductive biology of the mudskipper Apocryptes bato (Hamilton 1822) from the coastal waters of Chittagong, Bangladesh was conducted. Disproportionate occurrence of male and female (1.20 : 1) was observed in the number of two sexes. A prolonged spawning season was found from June to early October with a single peak. The aspects in the ovary indicate one complete spawning of females in a single spawning season. The fecundity was found to vary from 7453 - 31195 with an average of 17590 ± 6867. Significant coefficient of correlation between the diameters of the eggs of corresponding anterior, middle and posterior regions of the right and left ovaries indicated the simultaneous release of eggs from both the ovaries. A much closer relationship of fecundity and the significant ‘t’ values indicated fecundity increases with the increase of total length, standard length, body weight and gonad weight. Asiat. Soc. Bangladesh, Sci. 44(1): 91-99, June 2018